Kebijakan Penerapan Sanksi Pidana dalam Tindak Pidana Perdagangan Satwa Liar yang Dilindungi - Auliyani, Auliyani; Budiyanto, Budiyanto; Rohrohmana, Basir (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2023)
This study aims to reveal and analyze the comparative implementation of law enforcement against the crime of trade in protected animals in Indonesia, and to understand and analyze the form of policy recommendations on the crime of trade in protected wildlife in Jayapura City. The research method used focuses on normative juridical research by prioritizing secondary data sourced from primary legal materials, secondary legal materials, and tertiary legal materials, as well as statutory, conceptual, analytical approaches, legal history, and comparative legal approaches. The data obtained were processed using qualitative analysis techniques with three workflows; data reduction, data presentation, and verification (conclusion). The results of this study found that in a comparative analysis of cases of criminal acts of trade in protected wildlife that occurred in Aceh, Kalimantan, Surabaya, and Jayapura, the decisions against the defendants did not have a significant deterrent effect. The four cases show that the punishments given were lighter than the sanctions that should have been received according to the existing regulations. Even though the purpose of punishment for prevention, in reality, has not been fulfilled. This is because the penalty for the accused does not create a deterrent effect. Policy recommendations offered from the results of this study are the need for collaboration with stakeholders such as civil society, the private sector, local communities, and governments, and on a broad scale to stop the killing, trade, and demand for wildlife products. Then, strengthen institutional, legal, and regulatory systems to deal effectively with wildlife-related violations. In addition, in the implementation of these laws and regulations, it is necessary to ensure the effective monitoring and management of legal trade. Also, there must be a policy to prevent trade in protected wild animals which should give a deterrent effect to perpetrators based on security. Copyright Â© 2023 JEB. All rights reserved.